'Realities side by side': God's patience and Abraham's humanity in Genesis 18:16–33. Issue 2 (8th April 2016) - Wynne, Jeremy J.
Abstract: This paper argues that in Jesus Christ 'real humanity' is revealed as a gift of the patient God, who gives time and space to creatures. While Karl Barth's work in Church Dogmatics §30.3 focuses on God's patience as a mode of his redeeming presence, §44.3 opens up towards, but leaves undeveloped, a providential mode of patience, in which God constitutes his people by choosing them and giving them all they require to hear his Word and respond in obedience. Recognising God's patience in these distinct modes allows biblical instances of divine–human dialogue to be heard in new and compelling ways. For example, it allows Genesis 18:16–33 to be understood as foregrounding Abraham's joyful responsibility to engage with God, making that event, in all its contingency, the description of who Abraham is as real man. In this way, a complete theological anthropology has at its heart God's own perfection of patience.